STRATEGI KEPALA SEKOLAH DALAM MEWUJUDKAN PENDIDIKAN INKLUSIF YANG RESPONSIF TERHADAP KEBUTUHAN PESERTA DIDIK DI SD KABUPATEN PIDIE JAYA - Nana Puspita; Hera Yanti; Siraj Siraj (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to analyze principals’ strategies in realizing inclusive education that is responsive to students’ needs in elementary schools in Pidie Jaya Regency. Inclusive education is understood as an effort to fulfill every student’s right to obtain fair, equitable, and non-discriminatory educational services. This research employs a qualitative approach with a descriptive research design. The research subjects include principals and teachers from several elementary schools implementing inclusive education. Data were collected through in-depth interviews, observations, and documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings indicate that principals’ strategies in realizing responsive inclusive education include program planning based on the schools’ real conditions, the implementation of learning that is adaptive to students’ needs, and continuous evaluation through supervision and intensive communication with teachers and parents. Principals play a crucial role in managing resources, building an inclusive school culture, and encouraging collaboration among all school members. This study concludes that the success of inclusive education is strongly influenced by principals’ leadership that is responsive, adaptive, and oriented toward students’ needs